Comparative study of copper, zinc, iron, ferritin, calcium and magnesium levels in pregnancy induced hypertension and normotensive primigravida mothers - Biswas, Soumi; Roy, Abhishek; Biswas, Srabani (International Journal of Research in Medical Sciences, 2017)
Background: Exact pathophysiology of pregnancy induced hypertension (PIH) is still unknown but there is a definite relationship between trace elements and preeclampsia. Several studies in this context have conflicting reports. So, a comparative study of serum levels of copper (Cu), zinc (Zn), iron (Fe), ferritin, calcium (Ca) and magnesium (Mg), in PIH and normotensive primipara mothers was conducted. Methods: Study was conducted in Department of Biochemistry & Department of Gynaecology and Obstetrics, R. G. Kar Medical College & Hospital, Kolkata over 1 year from September 2013 to August 2014 on fifty PIH patients as cases and fifty normotensive primipara mother without proteinuria as controls, both having ages ranging between 15-35 years in 2nd and 3rd trimesters. Results: Serum Ca, Mg, Cu and Zn levels were found to be significantly reduced (<0.05) in the PIH group compared to the normal pregnant group. Serum ferritin was markedly increased in the cases (mean 90.41±47.39, p<0.00001). No significant correlation was found in serum Fe levels. Conclusions: Alteration of serum Cu, Zn, Ca, Mg and ferritin levels can be considered to have a role in the etiopathogenesis and severity of PIH.